2000
DOI: 10.1021/ol991312d
|View full text |Cite
|
Sign up to set email alerts
|

Convenient, in Situ Generation of Anhydrous Hydrogen Iodide for the Preparation of α-Glycosyl Iodides and Vicinal Iodohydrins and for the Catalysis of Ferrier Glycosylation

Abstract: [reaction: see text] Anhydrous hydrogen iodide is generated in situ by the reaction of solid iodine and a thiol. The HI thus generated has been employed for the efficient preparation of alpha-glycosyl iodides and vicinal iodohydrins from the corresponding glycosyl acetates and epoxides, respectively, and for Ferrier glycosylation of alcohols and thiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…To this end, galacto precursor 1 was treated with a mixture of I 2 and propandithiol, in accordance with the procedure described some years ago by Koreeda and co-workers for the in situ generation of anhydrous HI. [38] As expected, the reaction once more afforded free 4-OH galacto derivative 2 in high yield upon exposure to I 2 (0.6 equiv) and propandithiol (1.2 equiv; Scheme 2). Under these conditions, the reaction rate and yield were both similar to those observed with I 2 and Et 3 SiH.…”
Section: Resultssupporting
confidence: 69%
“…To this end, galacto precursor 1 was treated with a mixture of I 2 and propandithiol, in accordance with the procedure described some years ago by Koreeda and co-workers for the in situ generation of anhydrous HI. [38] As expected, the reaction once more afforded free 4-OH galacto derivative 2 in high yield upon exposure to I 2 (0.6 equiv) and propandithiol (1.2 equiv; Scheme 2). Under these conditions, the reaction rate and yield were both similar to those observed with I 2 and Et 3 SiH.…”
Section: Resultssupporting
confidence: 69%
“…In this context, many research groups have demonstrated reliable methods for generating glycosyl iodides from per ‐O ‐ acetylated sugars through treatment of trimethylsilyl iodide (TMSI) or HI equivalents . The instability of TMSI was addressed by Koreeda and co‐workers who utilized the possibility of the synthesis of anhydrous HI by the reaction of solid iodine with a thiol component in an organic solvent . In line with this, Field and co‐workers also generated TMSI in situ by reacting hexamethyldisilane (HMDS) with iodine .…”
Section: Glycosylationsmentioning
confidence: 99%
“…[1][2][3] However,H Ih as not been widely used in synthetic organic chemistry because of the limiteda vailability of anhydrous HI. [5][6][7] In addition, HI can also be prepared by thermald ecomposition of tertbutyl iodide (Scheme 1a). [5][6][7] In addition, HI can also be prepared by thermald ecomposition of tertbutyl iodide (Scheme 1a).…”
mentioning
confidence: 99%
“…[4] Thus,t he developmento fastandardm ethodf or the generation of anhydrous HI should advance synthetic chemistry.T he preparation of HI by the reduction of iodine with thiol or diphenylphosphine oxide and application to the CÀIb ond formation reactionhas been reported. [5][6][7] In addition, HI can also be prepared by thermald ecomposition of tertbutyl iodide (Scheme 1a). [8] However,asynthetic reactionu sing both the acidic and reductive nature of HI has been scarcely described.…”
mentioning
confidence: 99%